(untitled) (Global Journal of Computer Science and Technology, 2024)
The exact 3-satisfiability problem X3SAT is known to remain NP-complete when restricted to expressions where every variable has exactly three occurrences even in the absence of negated variables Cubic Monotone 1-in-3 SAT Problem The present paper shows that the Cubic Monotone 1-in-3 SAT Problem can be solved in polynomial time and therefore prove that the conjecture P NP holds